Mae Jemison - Calkhoven, Laurie; Dong, Monique (New York : Simon Spotlight, 2016)
A biography of Mae Jemison, the first female African-American astronaut.--
Early dreams -- Dreams on Earth -- Dreams about space -- Space! -- Life after space.
Keywords: Jemison, Mae, -- 1956- -- Juvenile literature; Jemison, Mae, -- 1956-; African American women astronauts -- Biography; Astronauts -- Biography -- United States; African American women astronauts -- Biography; Astronauts -- Biography -- United States; Biographies